DENYING THE PROBLEM. DEFLATIONISTS AND THE LIAR PARADOX - Paula-Pompilia TOMI (Studia Universitatis Babeș-Bolyai. Philosophia, 2018)
Deflationary theories of truth had two different types of responses to the Liar. A first class of deflationists considers that this paradox does not represent a problem for their theories. On the other hand, other deflationists find the Liar to be a serious issue. This article focuses on the first class. Both Grover and Gupta consider that the Liar does not represent a problem for a deflationary theory of truth. For Grover, the paradox is demolished through the construction of the theory and for Gupta, the Liar is not the problem of the deflationist, but rather it concerns a specialist. Dorothy Grover (2005) is an advocate of the prosentential theory of truth. This theory considers that truth works as a prosentence. The sentence resulted by adding the truth predicate to a referring expression has the same content as the sentence picked out by the initial referring expression. A prosentence does not have a meaning by itself; it takes its meaning from its antecedent. Grover considers that the truth predicate used in the Liar fails to pick up an antecedent, thus it does not have operative meaning. The operative meaning comes from using a word in a specific context. Gupta (2005) considers that a specialist – not a deflationist – should give the proper answers to the paradoxes. A deflationist should not be concerned with how the paradoxes can be avoided. His only interest is how the T-schema should be interpreted in order to give the meaning of the truth predicate and how the deflationary conclusions are reached. Paradoxes do not count in as an issue for deflationists, because they are able to answer to their main questions without facing paradoxes. Therefore, the Liar is not a real issue for the deflationist. The main aim of this article is to offer some counterarguments for these two views. Grover’s difference between dictionary and operative meaning seems to make a distinction between accepted and restricted sentences. This distinction is needed in order to escape the problem of paradoxes. If this is the case, the Liar is an issue, but it is solvable. This is quite different from what Grover claims. On the other hand, Gupta’s approach may ease the deflationist’s work but it might destroy his theory.